Komunitas Krustasea di Kawasan Mangrove Desa Jangkaran Kabupaten Kulon Progo - Sholihat Amalia; Djumanto Djumanto; Namastra Probosunu (Universitas Gadjah Mada, 2017)
The objective of this study was to determine the diversity and abundance of krustaseans in the mangrove area of Jangkaran Village, Temon District, Kulon Progo Regency. Sampling was done bi-weekly from October 2016 to February 2017 on six stations defined by ecological character. Krustasean sampling was done using cest net, trap net and hand picking along the river with the extent of each collection station about 10 m2. The captured krustasean samples were cleaned, stored in ice-cooled boxes and transported to the laboratories to be identified and grouped according to species, then measured by carapace length and individual weight. Observation of aquatic environment was done by measuring temperature, brightness, water depth, current velocity, pH, salinity, dissolved oxygen, and substrate type. The results of the observation obtained 1 order, 7 families, and 26 species. The family krustaseans found were Coenobitidae, Diogenidae, Grapsidae, Ocypodidae, Palaemonoidae, Penaeidae, and Portunidae. The most dominant species of krustaseans were white shrimp (Penaeus merguiensis) as much as 25.06%, hermit crab (Clibanarius sp.) as much as 10.85%, and Uca annulipes as much as 10.59%. The fewest species of krustaseans found were Varuna yui of 0.13% and Ocypode sp. as much as 0.26%. The abundance value was 25.4 ind / m2, indices of diversity 2.60, richess index 0.87 and index of dominance 0.18.